A regra da oitava como ferramenta de análise harmônica - Santos, André dos [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Many studies are being carried out on musical pedagogy from the 17th to the 19th century, opening the ways of understanding the repertoire of these centuries. One of the subjects about these researches is the Octave Rule as a practical musical learning tool. The Rule of Octave brings with it new insights into 17th century harmonic grammar, and possible developments throughout the 18th and 19th centuries. 20th and 21st century harmony manuals do not cite the Rule of Octave as a possible interpretation of harmonic analysis. The present work aims to make a simple comparison between Neapolitan Master Fedele Fenaroli's Rule of Octave; as basic rules for the movement of the bass, with Neapolitan Master Giovanni Furno, and the harmonic examples of the common practice repertoire labeled by Walter Piston.

Muitos estudos estão sendo feitos a respeito da pedagogia musical do século XVII até o XIX, abrindo caminho sobre outras maneiras de compreensão do repertório destes séculos. Um dos assuntos acerca dessas pesquisas é a Regra da Oitava como ferramenta de aprendizado musical prático. A Regra da Oitava trás consigo novos insights a respeito da gramática harmônica do século XVII, e possíveis desdobramentos ao longo do século XVIII e XIX. Manuais de harmonia do século XX e XXI não cita a Regra da Oitava como uma possível interpretação de análise harmônica. O presente trabalho, tem como objetivo fazer uma simples comparação entre a Regra da Oitava do Mestre Napolitano Fedele Fenaroli; as regras básicas de movimentação do baixo, com o Mestre Napolitano Giovanni Furno, e os exemplos harmônicos do repertório da prática comum cifrados por Walter Piston.
The rule of octave as a harmonic analysis tool
Keywords: Harmonia; Regra da oitava; Pedagogia harmônica; Contraponto